THE EUROPEAN MONITORING CENTRE FOR DRUGS AND DRUG ADDICTION - SELECTED SYSTEM-WIDE ISSUES AND ACTIVITIES - Woch, Katarzyna (Review of European and Comparative Law, 2018)
The issue of drugs is an important problem for the European citizens and it poses a serious threat to safety and health of the European society. This is mainly due to the fact that one of the basic features characterizing the problem of drugs is its changeable and dynamic nature. Furthermore, the drug-related phenomena have no borders, they exist everywhere where people live and affect all social classes. The European Union is one of the international organizations which, both by its own activities and the efforts of the member states, attempts to prevent and fight the adverse effects associated with drug abuse. The implementation of such a goal is possible thanks to the activities of the agency responsible for the holistic study of the problem of drugs and drug addiction and for popularization of the obtained information among the EU institutions, Member States and other organizations. The purpose of the article is to present the activities of the European Monitoring Centre for Drugs and Drug Addiction, whose role is to provide factual, objective, reliable and comparable information of the European standard on drugs and drug addiction as well as their effects both on the European Union itself and the member states.